Prevalence of Post-traumatic Stress Disorder After Flood: A Systematic Review and Meta-Analysis - Golitaleb, Mohamad; Mazaheri, Elaheh; Bonyadi, Mahtab; Sahebi, Ali (Frontiers in Psychiatry, 2022)
Abstract Introduction: Flood as the most common kind of the natural disasters has unpleased short, medium, and long-term consequences on the victims’ welfare, relationships, and physical and mental health. One of the most common mental health disorders in these victims is Post-Traumatic Stress Disorder (PTSD). The aim of this study is to investigate the prevalence of PTSD on the flood victims. Methods: Data resources including PubMed, Scopus, Web of Science, Science Direct, Embase, Google Scholar, conference and congress papers, key journals, the reference list of selected articles as well as systematic reviews were searched to identify studies that reported the prevalence of PTSD in flood victims. Random Effect Model was used to perform meta-analysis of the studies. Cochran test and I2 indicator were used to explore heterogeneity between the studies. Publication bias of the study was evaluated using Begg’test. Data were analyzed by STATA (version 14) software. Results: After a comprehensive search, 515 papers were extracted. After eliminating duplicates and final screening, 23 studies were selected and entered the meta-analysis phase after qualitative evaluation. The results showed that the prevalence of PTSD in flood victims is 29.48% (95% CI: 18.64-40.31, I2= 99.3%, p value < 0.001) Conclusion: The results of the present study showed that the prevalence of PTSD is relatively high in the flood victims. So, it is necessary to take preventive, supportive, therapeutic and effective actions for them.